An autonomous, low cost, distributed method for observing vehicle track interactions - Wolfs, Peter; Bleakly, S.; Senini, S.; Thomas, P. (IEEE, 2006)
Experience and field studies have shown that track geometry alone is not a good predictor of rail vehicle response. This paper describes a family of "Health Card" devices - an autonomous device that can be distributed on rolling stock to analyse the vehicle responses. As a distributed system is desired, and the intent is to apply this technology widely across a vehicle fleet, a low initial capital cost and low operating cost solution is desirable. As a consequence the Health Card performs all its sensing operations on the car body and avoids the costs and complications of sensing below the car body especially on unsprung components. Health Cards use solid-state transducers including accelerometers and angular rate sensors with a coordinate transform to resolve car body motions into six degrees of freedom. They then apply spectrogram techniques to obtain a time-frequency representation of the car body motion. These representations are autonomously analyzed to detect and classify transient dynamic events and to infer track degradation or operational risks